Comparative Analysis and Optimization of Separation Technique of Carboxylic Acid-Water Mixture Using Aspen Plus (Journal of Chemical Engineering Research Updates, 2025)
Acetic acid (ethanoic acid) is widely employed as a food preservative, a versatile solvent, and as an intermediate in the synthesis of various industrial chemicals. Recent studies have emphasized process intensification strategies for its separation. Conventional distillation, though straightforward, requires a large number of trays and significant energy input. In contrast, azeotropic and extractive distillation offer improved efficiency with fewer stages and lower energy demand. This study investigates the separation of acetic acid–water mixtures using azeotropic and extractive distillation. Among the azeotropic agents, isobutyl acetate demonstrated lower energy consumption and reduced total annual cost (TAC) compared to vinyl acetate, while achieving high product purity (98.6% acetic acid and 99% water). For extractive distillation, methyl tert-butyl ether (MTBE) exhibited superior performance, yielding 99% purity for both acetic acid and water with minimum energy requirement and solvent usage, outperforming ethyl acetate, which achieved 98.2% acetic acid and 99% water. In comparison, conventional distillation provided only 92.1% acetic acid and 86.4% water. Overall, extractive distillation with MTBE proved to be the most efficient and cost-effective option for acetic acid purification.
Keywords: Water; Acetic acid; Extractive distillation; Azeotropic distillation